Three new diterpenoids from the twigs and leaves of Croton laui. (February 2023) - Yang, Chengmin; Chen, Huiqin; Gao, Shuyi; Wang, Hao; He, Di; Cai, Caihong; Mei, Wenli; Liu, Shoubai; Dai, Haofu
Abstract: Three new diterpenoids, including one trachylobane (1 ) and two labdanes (2–3 ), were isolated from the aerial parts of Croton laui . Their structures were determined by analysis of their spectroscopic data. The absolute configuration of compound 1 was established by single-crystal X-ray diffraction analysis. Compounds 1–3 were assessed for cytotoxicity against A549, BEL-7402, SGC-7901, and Hela cell lines by the MTT assay. Compound 1 showed weak activity against the four human cancer cell lines with IC50 values of 36.09–93.94  μ M. Graphical Abstract: ga1 Highlights: Three previously unreported diterpenoids were isolated from Croton laui . The absolute configuration of compound 1 was established by single-crystal X-ray diffraction analysis. Compound 1 showed weak activity against K562 with IC50 value of 36.09 ± 0.43  μ M.